Safety of Antithymocyte Globulin in Patients Undergoing Liver Transplantation With Livers From Donation After Circulatory Death Donors. Issue 10 (October 2019) - Jorgenson, Margaret R.; Descourouez, Jillian L.; Felix, Daniel C; Hanlon, Bret M.; Leverson, Glen E.; Foley, David P.
Background: Studies suggest that rabbit-antithymocyte globulin (rATG) decreases biliary complications (BCs) after donation-after-circulatory-death-donor liver transplantation (DCD LTx), but safety data are lacking.Objective: Our aim was to assess the safety of rATG for this indication. The secondary end point was efficacy of rATG for this indication.Methods: Adult recipients of DCD LTx were divided into 2 cohorts: protocolized use of rATG in the modern era (July 1, 2013, to December 31, 2016) and a historical control without rATG (January 1, 2005, to June 30, 2013). Incidence of infection, leukopenia, and thrombocytopenia were compared for the safety assessment, incidence of BCs, ischemic cholangiopathy (IC), and transplant outcomes for the efficacy assessment.Results: A total of 83 patients met inclusion criteria: 42 in the historical cohort and 41 in the modern cohort. The modern cohort had significantly fewer bacterial infections at 3 months (historical 54.8% vs modern 23%; P = 0.004) and 1 year (historical 62.1% vs modern 34.2%, P = 0.004). The modern cohort also had fewer fungal infections at these time points (historical 33.3% and 47.9% vs modern 15% and 15%; P = 0.001). There were no significant differences in platelet or white blood cell reduction between groups. There was a nonsignificant, but numerical, trend toward reduced IC/BC in the modern cohort at 1 year (IC: historical 30.1% vs modern 13.2%, P = 0.08; BC: historical 51% vs modern 37.5%, P = 0.13). There was no difference in graft/patient survival.Conclusion and Relevance: Our data suggest no major safety issues with rATG in DCD LTx. Our study should ease clinical apprehension surrounding rATG use for this indication. Future prospective studies are needed to further evaluate the role of rATG and its impact on efficacy end points.